Plasma Lipoprotein(a) Levels and Atherosclerotic Renal Artery Stenosis in Hypertensive Patients - Cristiana Catena; GianLuca Colussi; Francesca Nait; Frine Capobianco; Leonardo A Sechi (Karger Publishers, 2015)
Background/Aims: The contribution of emergent cardiovascular risk factors to atherosclerotic renal artery stenosis (ARAS) is debated. We investigated the relationship of lipoprotein(a) and prothrombotic factors with ARAS in hypertension. Methods: In 50 hypertensive patients with angiographic evidence of ARAS and 58 hypertensive patients who had comparable cardiovascular risk factor burden but no evidence of renovascular disease, we measured renal function, lipoprotein(a), homocysteine, and hemostatic-fibrinolytic markers. Results: Patients with ARAS were more frequently smokers and had longer duration of hypertension, heavier antihypertensive treatment, and worse renal function than controls. Lipoprotein(a) was higher in patients with ARAS than controls, whereas no differences were found in homocysteine and all hemostatic variables. Multivariate analysis showed that lipoprotein(a) was associated with ARAS independent of other confounders including renal function and history of coronary heart, cerebrovascular, and peripheral artery disease. Conclusion: Lipoprotein(a) might contribute to the development of ARAS and detection of elevated levels of this lipoprotein could raise the suspicion of renovascular disease in patients with high blood pressure.